Brain aggregoma with clonal B-cell perivascular proliferation detected by next-generation sequencing. A case report and review of the literature - Alenka Matjašič; Karmen Wechtersbach; Rajko Kavalar; Matjaž Voršič; Jernej Mlakar; Janez Ravnik; Mara Popović (Folia Neuropathologica, 2021)
Light-chain deposition disease (LCDD), a rare type of monoclonal immunoglobulin deposition disease, can be presented as systemic or localized, very rarely affecting central nervous system (CNS). Only 10 cases of CNS-LCDD have been described so far. We present an eleventh case of cerebral tumour-like LCDD, called aggregoma, and compare it with previously reported cases. A 49-year-old patient was admitted to the hospital due to a first generalized epileptic seizure. Magnetic resonance imaging (MRI) showed focal lesion in the right occipital lobe. Abundant parenchymal aggregates of pale eosinophilic material were observed, Congo red negative, Thioflavin T moderately positive, and l-light chain positive, but k negative in immunofluorescence with mild perivascular lymphoplasmacytic infiltrates in the intervening brain tissue. Clonality testing by next-generation sequencing showed the monoclonal nature of B-lymphocytes. Electron microscopy showed a finely granular ultrastructure of the aggregates without deposition in the vessel walls. A whole-body workup did not show any extra-cerebral immune dyscrasias.